2018
DOI: 10.29332/ijpse.v2n3.188
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Bali traditional acoustic tools as physical repellent of bird pest on rice paddy crop

Abstract: The purpose of this research is to identify the diversity of Bali's traditional acoustic tools as a physical repellent of bird pest on rice paddy crop that characterizes local Balinese wisdom as well as analyze their existence and possible modification of tools. The method used is survey method through questionnaire and direct interview to farmers (age 60 years and over) in three rice paddy crop centers, namely Tabanan (6 villages), Badung (5 villages), and Gianyar (2 villages) regencies. Based on the survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Participants were selected by consecutive sampling in October 2020. Inclusion criteria were Indonesian males and females aged 60 years old and above which were screened for LS using the Indonesian version of the Loco-check 14 , could read and answer questionnaires in Indonesian language. Individuals were excluded if having any uncorrected eyesight disorders, hearing disorders, cognitive disorders, or hand grip disorders on dominant hand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were selected by consecutive sampling in October 2020. Inclusion criteria were Indonesian males and females aged 60 years old and above which were screened for LS using the Indonesian version of the Loco-check 14 , could read and answer questionnaires in Indonesian language. Individuals were excluded if having any uncorrected eyesight disorders, hearing disorders, cognitive disorders, or hand grip disorders on dominant hand.…”
Section: Methodsmentioning
confidence: 99%
“…The Indonesian version of the Loco-check was used as a screening tool to assess LS, which had been previously adapted for cross-cultural adaptation to Indonesian language 14 . The Loco-check consists of a 7-item questionnaire to assess locomotive disability based on the activities of daily living.…”
Section: Methodsmentioning
confidence: 99%
“…Out of the 127 respondents, 80.3% indicated that kepuakan is the most efficient order of acoustic tools, followed by pecut (10.2%), pindekan (8.7%), and kulkul (0.8%). All the traditional equipment is Balinese handicraft product [22].…”
Section: Ways Local Farmers Used To Handle Pest Birdsmentioning
confidence: 99%